THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, WORKLOAD AND JOB SATISFACTION ON TURNOVER INTENTION - Diana Situmorang, Evi; Kusuma Wardhani, Nia (Dinasti Publisher, 2022)
This study aims to analyze the transformational leadership style, workload and job satisfaction that effect employee turnover intention. The population of this study is employees at PT Dhanistha Surya Nusantara located in DKI Jakarta, with a sample of 117 workers whose determination is based on the use of the slovin formula. The data analysis method used the SPSS (Statistical Package for the Social Sciences) application. The result of the study is that transformational leadership has a significant negative impact on employee turnover intention. Workload has a significant positive effect on employee turnover intention. Job satisfaction has a significant negative effect on employee turnover intention, and transformational leadership, workload and job satisfaction have a simultaneous and significant effect on employee turnover intention.